Kualitas internal telur ayam ras yang direndam larutan daun kelor dengan lama penyimpanan selama 21 hari - Andi Triana; Muhammad Yunus; Nur Rasuli; Aminuddin Saade; Nurhana B (University of Insan Cendekia Mandiri, 2024)
This study aims to determine the quality of broiler chicken eggs soaked in Moringa leaf solution. This research was conducted by immersing purebred chicken eggs in Moringa leaf solution for 1 day and using a Completely Randomized Design (CRD) method with a sample of 80 purebred chicken eggs consisting of 4 treatments where each treatment consisted of 4 replications and each replication consists of 5 samples. Each treatment of the experimental design used in this study was P0 (without treatment), P1 (addition of 20% Moringa leaf solution), P2 (addition of 30% Moringa leaf solution), P3 (addition of 40% Moringa leaf solution). The variables observed were egg Kuningindex, egg white index and air voids.The results of the study showed that soaking chicken eggs in Moringa leaf solution at P3 (soaking in 40% Moringa leaf solution) had a real effect on the egg white index. The results of the extension evaluation carried out in the Pesona Mutiara Farmer Women's Group,